Ekonomin under omläggningsåren vid övergång till kravgodkänd produktion - Bienitzer, Per-Niclas (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2004)
The purpose of these theses is to show the financial economical situation during the change from conventional dairy production to ecological production. The thesis is accomplished by collecting information from literature and interviews where needed.